Comparison of Pre-Attentive Auditory Discrimination at Gross and Fine Difference between Auditory Stimuli - Sanju,Himanshu Kumar (2016)
Abstract Introduction Mismatch Negativity is a negative component of the event-related potential (ERP) elicited by any discriminable changes in auditory stimulation. Objective The present study aimed to assess pre-attentive auditory discrimination skill with fine and gross difference between auditory stimuli. Method Seventeen normal hearing individual participated in the study. To assess preattentive auditory discrimination skill with fine difference between auditory stimuli, we recorded mismatch negativity (MMN) with pair of stimuli (pure tones), using /1000 Hz/ and /1010 Hz/ with /1000 Hz/ as frequent stimulus and /1010 Hz/ as infrequent stimulus. Similarly, we used /1000 Hz/ and /1100 Hz/ with /1000 Hz/ as frequent stimulus and /1100 Hz/ as infrequent stimulus to assess pre-attentive auditory discrimination skill with gross difference between auditory stimuli. The study included 17 subjects with informed consent. We analyzed MMN for onset latency, offset latency, peak latency, peak amplitude, and area under the curve parameters. Result Results revealed that MMN was present only in 64% of the individuals in both conditions. Further Multivariate Analysis of Variance (MANOVA) showed no significant difference in all measures of MMN (onset latency, offset latency, peak latency, peak amplitude, and area under the curve) in both conditions. Conclusion The present study showed similar pre-attentive skills for both conditions: fine (1000 Hz and 1010 Hz) and gross (1000 Hz and 1100 Hz) difference in auditory stimuli at a higher level (endogenous) of the auditory system.